Systemic Juvenile Xanthogranuloma Involving the Bone Marrow, Multiple Bones, and the Skin That Developed During Treatment of Acute Lymphoblastic Leukemia in Remission State. (September 2018) - Cheon, Eunjae; Yang, Saemi; Han, Jae Ho; Lee, Kwang Chul; Park, Jun Eun
Juvenile xanthogranuloma (JXG) is a rare benign disorder classified as non-Langerhans cell histiocytosis, with unclear etiology and pathogenesis. JXG is generally characterized by solitary or multiple cutaneous nodules that resolve spontaneously over a few years. JXG rarely presents as extracutaneous lesions that progress to a symptomatic systemic disorder through multiple organ involvement. We encountered a systemic JXG case involving the bone marrow, multiple bones, and the skin during acute lymphoblastic leukemia (ALL) treatment. A 16-year-old boy undergoing ALL treatment experienced unexplained prolonged fever and scalp, hip joint, and right knee joint pain for 2 weeks during interim maintenance chemotherapy. Bone marrow pathologic findings revealed no evidence of leukemia relapse but showed diffuse infiltration of histiocytes with several Touton-type giant cells; the stains were positive for CD68 and negative for CD1a and S100 protein. Bone and skin biopsies confirmed the findings. Symptoms have resolved since maintenance chemotherapy, which included vincristine, dexamethasone, 6-mercaptopurine, and methotrexate. Bone marrow involvement of JXG is very rare, occurring only in patients less than 1 year of age; however, this case was reported in an adolescent during ALL treatment.